2014
DOI: 10.1080/13691058.2014.905706
|View full text |Cite
|
Sign up to set email alerts
|

‘Triply cursed’: racism, homophobia and HIV-related stigma are barriers to regular HIV testing, treatment adherence and disclosure among young Black gay men

Abstract: In the USA, young Black gay men are disproportionately impacted by HIV. In this qualitative study consisting of in-depth interviews with 31 young Black gay men and 9 service providers, where we used thematic analysis to guide our interpretations, we found that HIV-related stigma and homophobia, within the larger societal context of racism, were related to sexual risk behaviour, reluctance to obtain HIV testing or care, lower adherence to treatment medication, and disclosure of a positive HIV status to sexual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
234
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(254 citation statements)
references
References 18 publications
12
234
1
7
Order By: Relevance
“…Previous research has consistently related HIV-related stigma to negative outcomes, including poor medication adherence and greater HIV risk behavior [1216]. A recent qualitative study among young black MSM reported that HIV-related stigma and homophobia were related to sexual risk behavior, reluctance to obtain HIV testing or care, and poorer medication adherence [30]. An additional contributing factor may be the social class system unique to the US South that has traditionally allowed for little social mobility, along with marginalization of, and discrimination against certain groups and often resulting in distrust of systems of care among those in a lower social strata [31–33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has consistently related HIV-related stigma to negative outcomes, including poor medication adherence and greater HIV risk behavior [1216]. A recent qualitative study among young black MSM reported that HIV-related stigma and homophobia were related to sexual risk behavior, reluctance to obtain HIV testing or care, and poorer medication adherence [30]. An additional contributing factor may be the social class system unique to the US South that has traditionally allowed for little social mobility, along with marginalization of, and discrimination against certain groups and often resulting in distrust of systems of care among those in a lower social strata [31–33].…”
Section: Discussionmentioning
confidence: 99%
“…These studies, however, have only focused on individual-level factors. Neighbourhood characteristics are important considerations for HIV prevention outcomes,9 especially for YBMSM who have historically experienced high social segregation due to racism and homophobia 10. For example, neighbourhood physical and social disorder such as high violent crime, dense alcohol outlets and extensive vacant building can be structural stressors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Arnold, Rebchook, and Kegeles (2014), speak to the experience of Black, gay, HIV-positive young men feeling “triply cursed” via marginalization in their Black communities and families for their sexual identity and/or HIV status, while also struggling with broader societal racism. While these perspectives are from young adults, the experiences of losing support or being outright attacked often reach back to key developmental periods during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…While these perspectives are from young adults, the experiences of losing support or being outright attacked often reach back to key developmental periods during adolescence. Such experiences of alienation and/or rejection from within the Black community can result in Black GBT youth enacting coping mechanisms that can place them at higher risk for HIV and STIs, such as increased sexual risk behaviour and reluctance to obtain HIV testing (Arnold et al, 2014). This is evidenced by the United States’ Centers for Disease Control and Prevention (CDC) estimate that Black young men who have sex with men accounted for 75% of all new U.S. HIV infections among adolescents ages 13–19 in 2008 (2011).…”
Section: Introductionmentioning
confidence: 99%